Pelatihan Outseal-Haiwell for PLC and SCADA di SMKN 1 Singosari, Malang - Denny Irawan; Rini Puji Astutik; Eka Putra Prastya; Alief Hidayah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Advances in automation technology in industries that run very fast have spurred every educational institution to be able to keep up. Every SMK is no exception, which is tasked with preparing and producing students to be able to compete in the world of work. One of the automation technologies is PLC and SCADA which are widely used in the industrial world, for this reason, it is necessary for Muhammadiyah Gresik University students, especially the Electrical Engineering study program, to share knowledge about one of the PLCs and SCADA by using Outseal as PLC and Haiwell as SCADA at SMKN Singosari, Malang in the form of community service activities. By providing training on the basics of PLC and SCADA using Outseal software as a PLC which is uploaded to Arduino and Haiwell as an HMI for SMK students in understanding the basics of PLC which is then followed by simulating cases that often occur in the industry. The results of the student response were very positive giving an assessment of more than 90% and wanting a similar training with a different theme.